Estilos de vida y estado nutricional del personal administrativo de la facultad de medicina de la Universidad Nacional de Trujillo - Chávez Galarreta, Josimar Alejandro (2020)
The present investigation of non-experimental type and transversal descriptive-analytical design aims to identify if there is an association between the lifestyles and the nutritional status of the administrative staff of the Faculty of Medicine of the National University of Trujillo. The study population consisted of fifty-five people who met the selection criteria. Data collection was performed using a standardized height and balance scale for the Body Mass Index and an instrument on the practice of healthy lifestyles. The result was that there is no significant association between lifestyles and nutritional status in the administrative staff of the Faculty of Medicine of the National University of Trujillo. This allows concluding that there is no association between lifestyles and the nutritional status of the administrative staff of the Faculty of Medicine of the National University of Trujillo, that is, it does not correlate significantly, however, there is a high relationship between these variables studied.